Cicerono Ketvirtoji Filipika: monologo virsmas dialogu - Kučinskienė, Audronė (Literatūra, 2007)
The publication consists of the first published translation of Cicero’s Fourth Philippic into Lithuanian, accompanied by an article which analyses the phenomenon of dialogicity in the rhetorical speech as a literary genre. The reaction of the audience, incorporated into the text of the speech, creates the semblance of a dialogue between the orator and his listeners. The Fourth Philippic is the best extant example of this phenomenon, as the reaction of the audience here functions not only in certain individual episodes of the speech, as is the case in other Cicero’s speeches, but becomes the principal rhetorical device on which the whole strategy of the speech is built. We argue that by emphatic interpretation of the audience’s reaction as full and unanimous assent to his statements, Cicero intends to theatrically convey the main message of the speech: the apparent consensus between the people and the senate, as well as his own role as the leader of the Roman people.